Comparison of Friedewald’s formula, modified Friedewald’s formula and Anandaraja’s formula with direct homogenous serum LDL cholesterol method in CHD patients - P., Brindha Devi; T., Ilanchezhian; D., Sarguru; S., Ayyappan; R., Karnaboopathy; Karnik, Aarti; A., Saddam Hussain (International Journal of Research in Medical Sciences, 2020)
Background: Elevated serum Low-Density Lipoprotein Cholesterol (LDL-C) concentration is a well-known atherogenic risk factor with a high predictive value for coronary heart disease. An important aspect of the assessment of coronary heart disease risk for a dyslipidemic subject is the estimation of serum Low-Density Lipoprotein Cholesterol (LDL-C). There are many homogenous assays currently available for the estimation of serum LDL-C. Most clinical laboratories determine LDL-C (mg/dl) by Friedewald’s formula (FF), LD-=(TC)-HDL-C)-(TG/5), Modified Friedewald’s formula (MFF), LDL-C=(TC)-(HDL-C)-(TG/6), Recently Anandaraja and colleagues have derived a new formula for calculating LDL-C, AR-LDL-C=0.9 TC-(0.9 TG/5)-28. Methods: It is cross-sectional study. Lipid profile data was collected from known of CHD patients, who had come for lipid profile investigation to the Central Biochemistry laboratory of ACPM Medical College and hospital. LDL-C estimation was done by direct homogenous assay and also calculated using the Friedewald’s Formula, Modified Friedewald’s Formula and Anandaraja’s Formula for assessing and validity of the LDL cholesterol. Results: From the present study, The LDL-FF, MFW and AR are increased with levels of TGL > 200 mg/dl and decreased level of TC < 200 mg/dl seem to interfere with the estimation of Direct LDL cholesterol Conclusions: Authors conclude that, LDL-C by direct method is most reliable and sensitive in CHD patients compare with FF, MFW, and ARF.